Analyze the Chosen Production Criteria of Carrier Pigeons - Martin Fik; Cyril Hrnčár; Henrieta Arpášová (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this work was to analyze the chosen production criteria of carrier pigeons. We observed the weight of the squabs on the 28th day and their weight before the slaughtering. The slaughtering was carried out before and after the young pigeons left the nest. We recorded the squabs´ growing intensity and weekly weight gain in the nest (1st – 35th day), live weight before the birds were slaughtered, the weight after the birds were slaughtered (defeathered and decapitated birds), the carcass weight (defeathered, decapitated and with internal organs retracted birds) and dressed weight (%). The pigeons’ average weight was 396. 85 g (min. 292. 00 g, max. 489.00 g) when they were 4 weeks old. The average pigeons’ weight recorded before leaving the nest and slaughtering was 427.42 g (min.335.00 g, max. 502.00 g).  The average pigeons’ weight recorded before leaving the nest, but after the slaughtering (defeathered, decapitated birds after bleeding) was 369.46 g (min. 308.00 g, max. 441.00 g). The average pigeons’ weight recorded after leaving the nest, but before slaughtering was 482.88 g (min. 413.00 g, max. 560.00 g). The average pigeons’ weight recorded after leaving the nest and slaughtering (defeathered, decapitated birds after bleeding) was 407.75 g (min. 321.00 g, max. 503.00 g). The average weigh on hatch day was 19.63 g (min. 18.00 g, max. 20.00 g). After 7 days, the pigeons‘average weight was 101.38 g (min. 89.00 g, max. 104.00 g). The average weight of 14 days old pigeons was 213.38 g (min. 163.00 g, max. 261.00 g). The average weight of 21 days old pigeons was 295.63 g (min.234.00 g, max. 347.00 g) and the average weight of 28 days old pigeons was 358.13 g (min. 292.00 g, max. 412.00 g). The last weighting was recorded on the 35th day and the average pigeons ‘weight was 397.13 g (min. 350.00 g a max. 426.00 g). Before the pigeons left the nest the carcass weight was 275.42 g (min. 182.00 g, max. 335.00 g). After the pigeons left the nest the carcass weight was 316.56 g, (min. 260.00 g, max. 359.00 g). Before leaving the nest pigeons’ dressed weight presented 64.09 %, (min. 54.33 %, max. 70.40 %) of the observed criterion and after leaving the nest pigeons’ dressed weight presented 65.51 %, (min. 54.87 %, max. 68.13 %) of  the observed criterion.